ANALYZING THE ROLE OF SOCIAL MEDIA IN SHAPING STOCK MARKET INVESTMENT CHOICES - Anika; Ahlawat, Pardeep K. (International Journal of Research -GRANTHAALAYAH, 2025)
Social media has played a dominant role in influence the manner in which decisions in stock markets are made, investor moods, market volatility, and the overall financial decision-making. The availability of real-time access to an assortment of opinions, market forecasts and discussions, found on Twitter, Reddit and LinkedIn, exposed investors to a broad variety of views and market speculation that can quickly influence the price of a stock. This means that social media leads to timely sharing of information that can strengthen a positive or negative sentiment in the market compared to traditional media. As shown through the GameStop short squeeze, online forums, like Wall Street Bets on Reddit, are capable of producing dramatic shifts in stock prices, often on just opinion rather than when considering company fundamentals. But this democratization of financial information has its potential risks whereby there is misinformation, decision making emotionally and the ability to manipulate the market. The investors are now subjected to collective group think and herd behavior that can result in speculative bubbles and volatility. In this paper, we shall discuss the effects of social media on stock market choices, its effects compared to conventional media and the way it has changed the contemporary modern choice in stock market. It emphasizes the importance of investor attitude in the change of the price of the stock and the consequences of social media on the stance of retail investors, behavioral finance, and market efficiency.